‘Merantau’ - an Informal Entrepreneurial Learning Pattern in the Culture of Minangkabau Tribe in Indonesia - Hafiz Rahman (Universitas Pelita Harapan, 2016)
The aim of this paper is to expose an informal entrepreneurial learning pattern that is undertaken by the Minangkabau tribe in Indonesia and relate it to cultural dimension and perceived value of a society. This informal entrepreneurial learning pattern is called as ‘Merantau’ - which can simply be meant as ‘to emigrate’, in which the young males (mostly during the ages of 15-20, or even younger) leave their homeland; move to other places nationwide or abroad, and running entrepreneurial activities for their daily life. The existence of merantau as an informal cultural based entrepreneurial learning for the young Minangkabau tribe combined with their cultural dimension and perceived values have contributed to the creation of and bring positive impacts to entrepreneurial culture of the Minangkabau tribe.The Minangkabau tribe, as one of tribes in Indonesia, experiences very supportive social environment in which entrepreneurial culture is recognised as part of the way of life. Therefore, Minangkabau tribe is known as one of the most entrepreneurial tribes in Indonesia.This paper considers perceived value and cultural dimension that may bring consequence to entrepreneurial culture of a society, with particular analysis to Minangkabau tribe in Indonesia. Analysis is undertaken by considering the elements and index of cultural dimension and perceived values of a society that can create and intiate entreprenuerial habits and relate them to entrepreneurship.Result of the analysis shows an evidence that culture of a society also plays an important role to create and maintain entrepreneurial habits and experience of a society. Together with cultural dimension of a society, perceived values that a society has, also contributes to the creation of entrepreneurial culture of that society. This is shown in the context of the Minangkabau tribe who is well known as an entrepreneurial tribe in Indonesia. However, this study analyses one single cultural background from a specific tribe in Indonesia and since it was undertaken to a single cultural background, it will be worth to extend this study and investigation into several cultural and value backgrounds from various ethnic groups/tribes in Indonesia or any other countries. Comparatively, this will add knowledge and dimension regarding entrepreneurship and its relationship to cultural dimension and perceived values of a society/community/ethnic group.